A Rapid Effervescent Route to Rational Activation of Cu/g‐C3N4 and bulk MoS2 Cocatalyst for Highly Efficient and Robust Photo‐Fenton Process. Issue 35 (10th October 2022) - Li, Wenxin; Ding, Chenjie; Kang, Shifei; Gao, Weikang; Yang, Yang; Cui, Lifeng
Abstract: Heterogeneous Fenton‐like process with a wide pH range is a promising alternative to traditional homogeneous Fenton reactions. Recently, the boosting effect of MoS2 cocatalysts is widely recognized in Fenton reactions, and the primary mechanism is the promotion of the reduction and recycling of high‐valence metal ions. Unfortunately, integrating heterogeneous Fenton‐like catalysts and MoS2 cocatalyst to form an efficient system remains challenging due to the severe deactivation of MoS2 and the inability of simple physical mixing to speed up the reaction. For the first time, the direct activation of commercially available bulk MoS2 powder in a durable acidic microenvironment is achieved. The foam‐modified photo‐Fenton catalyst (Cu‐CN‐ef) promotes the rapid activation and formed an ideal MoS2 ‐excited photo‐Fenton system. The significant synergistic effect of the system is ascribed to the outstanding sustainability of Cu‐Mo redox cycling and favorable local acidic microenvironment on the surface of Cu‐CN‐ef. This system works well in outdoor cases with a tiny amount of commercially available Cu‐CN/MoS2 powder, promising a new route for portable and rapid solar‐powered wastewater treatment. The unique effervescence modification method shows great potential in the rational reconstruction of the affinity interface of composite catalysts and efficient solar energy utilization systems. Abstract : For the first time, the direct activation of commercially available bulk MoS2, forming an ideal photo‐Fenton system is achieved. The main reason for the synergistic effect is the enhanced sustainability of Cu‐Mo redox cycle and the excellent local acidic microenvironment on the surface of Cu‐CN‐ef. In addition, the system can work well in outdoor environment.